Peran Teknologi Digital Dalam Meningkatkan Daya Saing UMKM Ekonomi Kreatif Berbasis Budaya di Kawasan Medan - Jhon Martin Putra Siregar; Lailan Syafrina Hasibuan; Wina Nurfitriani; Rangga Wardana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
This study examines the impact of technological innovation on the competitiveness of micro, small, and medium enterprises (MSMEs) in Medan City. The main objectives of the study include: (1) understanding the role of technological innovation in increasing the competitiveness of MSMEs in local and international markets, (2) analyzing the types of significant technological innovations, and (3) determining the influence of innovation on operational efficiency, product quality, and customer service. The method used was a descriptive qualitative approach with a purposive sampling technique, involving interviews with five MSME owners. The results show that technological innovations, such as digital applications (e.g., si KEdan) and social media, have a positive impact on the competitiveness of MSMEs, particularly in the culture-based creative economy sector. The use of printing methods in fashion production also contributes. However, challenges such as legality and operational standards have not been overcome. Government support, including training and technical assistance, is crucial to facilitate the implementation of digital technology so that MSMEs in Medan City can develop better. This study emphasizes the importance of collaboration between MSMEs and the government to strengthen innovation and competitiveness in the digital era.